KONSUMSI TABLET BESI TERHADAP KADAR HEMOGLOBIN IBU HAMIL TRIMESTER DUA - Sari, Anjelina Puspita (Poltekkes Kemenkes Palembang, 2020)
Background: Pregnant women with anemia in Palembang in 2014 were 1,028 (3.0%) out of 33,309 pregnant women, the coverage of Fe1 (30 tablets) for Palembang in 2017 was 99.12%, the lowest coverage of Fe-1 in Kecamatan Ilir Timur I. This study aimed to determine the effect of iron consumption with hemoglobin level in second trimester pregnant women. Methods: This type of observational analytical study used pretest and posttest control group design. The population in this study was all pregnant women in the working area at Kecamatan Ilir Timur I of Palembang which were conducted from November 2019-January 2020. The number of samples was 16 respondents. The sampling technique is total sampling. Data analysis technique was Paired Sample T-Test analysis. Results: The results showed that the average hemoglobin levels in second trimester pregnant women after consumption of 30 iron not significant differences in mean hemoglobin level (11.96±0,67 g/dl) compared to pregnant women who had not consumed iron (12.26±0.99 g/dl) with p value =0,079 (>0,05), however, keeping hemoglobin levels within normal limits. Conclusion: Based on the results, it is recommended that Health workers continues to promote iron tablets especially pregnant women in accordance with the government program, which is 90 tablets during pregnancy.